MACROECONOMIC FACTORS AND SMEs PERFORMANCE IN NIGERIA (1992-2021) (Journal of the Management Sciences, 2023)
The study examined the impact of macroeconomic factors on the performance of small and medium-scale enterprises (SMEs) in Nigeria for a period of 30 years (1992 - 2021). The main objective of this study was to examine how macroeconomic factors have influenced the performance of small and medium-scale enterprises in Nigeria. The dependent variable was the performance of SMEs, while the independent variables were Gross Domestic Product (GDP), Foreign Direct Investment, Export trade, and Inflation rate. The study was anchored on Keynesian Theory. The study used data from the Central Bank of Nigeria's Statistical Bulletin and subjected them to multiple regression analysis. The findings of the study revealed that there is a significant relationship between GDP and SME performance in Nigeria. Also, Export had a negative insignificant relationship with SMEs performance in Nigeria. And that the inflation rate had a positive but insignificant relationship with SMEs performance in Nigeria. While Foreign Direct Investment had a positive and significant relationship with SMEs performance in Nigeria. The study conclude that macroeconomic factors had mixed effects on SMEs performance in Nigeria. The study, therefore, recommended that the Central Bank of Nigeria should formulate policies to stabilize macroeconomic factors, thereby affecting the performance of SMEs positively.
Keywords: FDI; GDP; Export Trade; Inflation; SMEs